Strategi Pemasaran Pt. Huawei Dalam Meningkatkan Pangsa Pasar - Nicolas Septian dan Chairy (Universitas Tarumanagara, 2019)
In this era, everyone is very dependent on cellphones, especially smart phones. With the fourth most populous population in the world and the low adoption rate of smart phones, the smartphone market is an attractive market for local vendors and international vendors. As one of the world's biggest vendors, Huawei has difficulty facing competition in the Indonesian market. Therefore, the purpose of this thesis is to arrange and suggest a proper marketing strategy for the company. Data collection methods were interviews and observations. Writing starts from the analysis of external, internal, and industrial environments, SWOT analysis, and BCG matrix analysis.